Architectural Design for All - Dhamma–Damrong, Kusuma (Journal of Architectural/Planning Research and Studies (JARS), 2002)
In today’s Thai society, all people have equal rights and opportunities. Everyone has a chance to earn his/her own living, to study, to communicate, and to enjoy both private and public space. However, without the provision of physical elements in universal design accessible for all people such as transportations, infrastructures, neighborhoods, or buildings, a lot of people will absolutely suffer and lose their opportunities. The contents of this paper derive from 4 main sources: UN-ESCAP Guidelines on Promotion of Non Handicapping Physical Environments for Disabled Persons, the psychological insights from Dr. Prapod Patragas in the article “World Wide for Disabled Persons”, the 1991 Rehabilitation of Disabled Persons Act, and the 2001 Regulations on Provision of Equipment and Accommodation for the disabled. All the information has been analyzed to achieve the appropriate approaches and recommendations for planning and designing accessible environments for all types of disabled.